Endothelial and tumor-intrinsic mechanisms of hepatic melanoma metastasis - Wohlfeil, Sebastian A.; Géraud, Cyrill (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
The treatment of metastatic cutaneous melanoma was fundamentally improved by the discovery and introduction of immune checkpoint inhibitors, such as anti-PD-1 and anti-CTLA-4 antibodies, and targeted therapy with BRAF and MEK inhibition. Unfortunately, many patients suffer a relapse due to resistance mechanisms that in part are mediated by organ-specific metastatic sites. Especially, brain and liver metastases are negative predictive factors for both treatment modalities. There is still high unmet clinical need to prevent and treat spread to these organs. Therefore, experimental research should focus on mechanisms of hepatic melanoma metastasis to better understand this process and to identify therapeutic targets.